A model of the effect of fungicides on disease-induced yield loss, for use in wheat disease management decision support systems - Milne, Alice E.; Paveley, Neil; Audsley, Eric; Parsons, David J. (Blackwell Publishing Ltd., 2007)
A model of the effect of foliar-applied fungicides on disease-induced yield loss is described, parameterised and tested. The effects of fungicides on epidemics of Septoria tritici (leaf blotch), Puccinia striiformis (yellow rust), Blumeria graminis f.sp. tritici (powdery mildew) and Puccinia triticina (brown rust) on winter wheat were simulated using dose-response curve parameters. Where two or more active substances were applied together, their joint action was estimated using an additive dose model where the active substances had the same mode of action or a multiplicative survival model where the modes of action differed. By coupling the model with models of wheat canopy growth and foliar disease published previously, it was possible to estimate disease-induced yield loss for a prescribed fungicide programme. The difference in green canopy area and, hence, interception of photosynthetically active radiation between simulated undiseased and diseased (but treated) crop canopies was used to estimate yield loss. The model was tested against data front field experiments across a range of sites, seasons and wheat cultivars and was shown to predict the observed disease-induced yield loss with sufficient accuracy to support fungicide treatment decisions. A simple method Of accounting for uncertainty in the predictions of yield loss is described. Fungicide product, dose and spray timing combinations selected using the coupled models responded appropriately to disease pressure and cultivar disease resistance.